A history of poly A sequences: from formation to factors to function - Edmonds, Mary (Progress in Nucleic Acid Research and Molecular Biology, 2002)
Biological polyadenylation, first recognized as an enzymatic activity, remained an orphan enzyme until poly A sequences were found on the 3′ ends of eukaryotic mRNAs. Their presence in bacteria viruses and later in archeae (ref. 338) established their universality. The lack of compelling evidence for a specific function limited attention to their cellular formation. Eventually the newer techniques of molecular biology and development of accurate nuclear processing extracts showed 3′ end formation to be a two-step process. Pre-mRNA was first cleaved endonucleolytically at a specific site that was followed by sequential addition of AMPs from ATP to the 3′ hydroxyl group at the end of mRNA. The site of cleavage was specified by a conserved hexanucleotide, AAUAAA, from 10 to 30 nt upstream of this 3′ end. Extensive purification of these two activities showed that more than 10 polypeptides were needed for mRNA 3′ end formation. Most of these were in complexes involved in the cleavage step. Two of the best characterized are CstF and CPSF, while two other remain partially purified but essential. Oddly, the specific proteins involved in phosphodiester bond hydrolysis have yet to be identified. The polyadenylation step occurs within the complex of poly A polymerase and poly A-binding protein, PABII, that controls poly A length. That the cleavage complex, CPSF, is also required for this step attests to a tight coupling of the two steps of 3′ and formation. The reaction reconstituted from these RNA-free purified factors correctly processes pre-mRNAs. Meaningful analysis of the role of poly A in mRNA metabolism or function was possible once quantities of these proteins most often over-expressed from cDNA clones became available. The large number needed for two simple reactions of an endonuclease, a polymerase and a sequence recognition factor, pointed to 3′ end formation as a regulated process. Polyadenylation itself had appeared to require regulation in cases where two poly A sites were alternatively processed to produce mRNA coding for two different proteins. The 64-KDa subunit of CstF is now known to be a regulator of poly A site choice between two sites in the immunoglobulin heavy chain of B cells. In resting cells the site used favors the mRNA for a membrane-bound protein. Upon differentiation to plasma cells, an upstream site is used the produce a secreted form of the heavy chain. Poly A site choice in the calcitonin pre-mRNA involves splicing factors at a pseudo splice site in an intron downstream of the active poly site that interacts with cleavage factors for most tissues. The molecular basis for choice of the alternate site in neuronal tissue is unknown. Proteins needed for mRNA 3′ end formation also participate in other RNA-processing reactions: cleavage factors bind to the C-terminal domain of RNA polymerase during transcription; splicing of 3′ terminal exons is stimulated by cleavage factors that bind to splicing factors at 3′ splice sites; nuclear export of mRNAs is linked to cleavage factors and requires the poly A II-binding protein. Most striking is the long-sought evidence for a role for poly A in translation in yeast where it provides the surface on which the poly A-binding protein assembles the factors needed for the initiation of translation. This adaptability of eukaryotic cells to use a sequence of low information content extends to bacteria where poly A serves as a site for assembly of an mRNA degradation complex in E. coli. Vaccinia virus creates mRNA poly A tails by a streamlined mechanism independent of cleavage that requires only two proteins that recognize unique poly A signals. Thus, in spite of 40 years of study of poly A sequences, this growing multiplicity of uses and even mechanisms of formation seem destined to continue.